(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Especially in the history of the Uzbek people of Central Asia - the era of the khanates has a special place. In the thousand-year history of the Uzbek people, this period is distinguished not only by its duration, but also by the great events that took place in the social and political life of our people. After the death of Timur, the incessant wars between the Timurid princes led to the disintegration of the powerful state that the master had built with great difficulty. Gradually, a number of states and estates separated from this powerful state. The Turkmens, located in a wide area from Khorezm to Astrobad, were the first to break away from the Timurid state. At the same time, the Ferghana Valley became independent. Also, Hisar and Badakhshan became independent states. As a result, the Timurid state fell not only in Central Asia, but also in Khorasan and Iran. This article reveals the historiography of the management policy of the Shaibani state in Bukhara during the rule of the Uzbek khanates.